Barriers to the early integration of palliative home care into the disease trajectory of advanced cancer patients: A focus group study with palliative home care teams. (19th February 2019) - Dhollander, Naomi; De Vleminck, Aline; Deliens, Luc; Van Belle, Simon; Pardon, Koen
Abstract: Objectives: Palliative care is still often involved late in the disease trajectory. Recently, some studies have explored the barriers to early integration of PC in the hospital setting. Because palliative care home care (PHC) is organised differently compared with PC in a hospital setting, the identification of barriers to the early integration of PHC is needed. Methods: Six focus groups were held with PHC teams in Flanders, Belgium. Discussions were transcribed verbatim and analysed using constant comparative analysis. Results: Our findings confirm many barriers found in previous studies, such as the lack of financial resources and the perception of PC as terminal care. Oncologists' lack of knowledge about the content and role of PC is also confirmed. Furthermore, professional caregivers working in the home context are lacking information on oncology therapies necessary to provide optimal PC. A barrier for the home context is the discontinuity of care, as a result of a lack of communicational structure and a lack of central coordination. Conclusion: The results contribute to a better understanding of the factors hindering the provision of PHC alongside oncology care. For the home context, transmural discontinuity of care seems to be an important additional barrier.